Sufi Qurʾān Commentaries, Genealogy and Originality: Universal Mercy as a Case Study - Coppens, Pieter (Journal of Sufi studies, 2018)
This article reflects on some methodological issues in the study of tafsīr, taking the dissemination of the ideas of Ibn ʿArabī (d. 638/1240) on the non-perpetuity of the chastisement of Hell in Sufi tafsīr as a case study. I show that Ibn ʿArabī's ideas on the issue were hardly adopted by later Sufi commentators on the Qurʾān. I investigate whether just as its exoteric counterpart, and despite the claim of Sufi tafsīr being rooted in experience' and thus being more original', Sufi tafsīr is genealogical' and is thus more conservative in its content. Although the Sufi genre of tafsīr generally seems more willing to include Sufi sayings and ideas from outside the boundaries of the genre, this does not make it adaptive of the non-mainstream ideas of Ibn ʿArabī on Hell proposed outside the genre. This brings up some considerations on the use and usability of tafsīr as a source of intellectual history.